Time trend of hospitalization due to burn, in the age group of 0-14 years, in Brazil, 2012-2022 - Luzieli Portaluppi; Caroline Silva Bettiol; Andreia Clara Nazário; Nazaré Otília Nazário (Revista Brasileira de Cirurgia Plástica)
Introduction: Burns are tissue injuries caused by contact with heat sources. They represent a global public health problem. They have major impacts on children. The severity and intensity of burns are related to the etiological agent and their consequences are a major obstacle for the patient. Method: The study analyzed data on hospital admissions for burns in children from 2012 to 2022, using information from SIH-SUS. Hospitalization rates per 100,000 inhabitants were calculated for each year, considering dependent variables. The researchers used standardized coefficients and simple linear regression to analyze the data. Results: Data from 91,091 hospitalizations for burns in children, 0-14 years old, were included. There was stability in the general hospitalization rate (mean rate 17.963; ß = 0.119; p = 0.163). In females there was an increasing trend (mean rate 14.346; ß = 0.169; p = 0.029); in males, there was stability (mean rate 21.426; ß = 0.069; p = 0.504). Females behaved with stability in all age groups; the male with an increase in the range 0-4 years (mean rate 42.264; ß = 0.613; p = 0.003), stability in the range 5-9 years (mean rate 14.189; ß = -0.21; p = 0.867) and reduction in the range 10-14 years (mean rate 9.871; ß = -0.328; p = 0.007). The South Region demonstrated an increasing trend (mean rate 26.952; ß = 1.091; p = 0.001). Conclusion: There was stability in the general hospitalization rate. The female sex tended towards increase and the male towards stability. There was stability in Brazilian regions, except in the South.